Pemahaman Konsep Matematika Siswa Ditinjau dari Kecerdasan Emosional dan Spasial - Maria Asti; Gunur, Bedilius; Silfanus Jelatu; Apolonia Hendrice Ramda (Unika Santu Paulus Ruteng, 2022)
Conceptual understanding is one of the core standards in mathematics or as a key component of mathematical skills. Understanding mathematical concepts is knowledge that involves a thorough understanding of the underlying concepts and the basis behind the algorithms performed in mathematics. A student must have this understanding if he wants to understand mathematics in depth. The problem may not be because it is solely related to the learning process, but rather the internal intelligence of students. This study examines how the relationship between spatial and emotional intelligence with students' understanding of mathematical concepts. This research is a correlational research with multiple correlation research design. This research involved 66 students of SMP class VIII in Kab. East Manggarau, NTT as a sample. Data collection is done by using questionnaires and tests. Before the data were analyzed correlatively, both simple and multiple, the analysis prerequisite tests were carried out, namely normality, linearity, and multicollinearity. The results of data analysis show that these three test requirements are met and the results of hypothesis testing indicate that there is a positive and significant relationship between emotional and spatial intelligence and students' understanding of mathematical concepts (either partially or simultaneously). Simultaneously, these two intelligences contribute 16.08% to increasing students' understanding of mathematical concepts. The study provides a recommendation that in improving students' understanding of mathematical concepts, consideration of students' basic intelligence factors needs to be considered before being treated or designing a mathematics learning environment